2023
DOI: 10.1039/d2dt03714a
|View full text |Cite
|
Sign up to set email alerts
|

A multi-cation responsive Ni(ii)-supramolecular metallogel mimics a molecular keypad lockviareversible fluorescence switching

Abstract: Synthesis of a bidentate N,O-donor Schiff base fluorescent ligand 5-(diethylamino-2-((4-(diethylamino-2-((4-(diethylamino)phenylimino)ethyl)phenol) (HL) adopting new preparation procedure and its complexes with Ni(II) (1) and Zn(II) (2), has been illustrated. Structures of HL...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Zn(II), Cu(II), and Hg(II) : The article by Pandey et al showed the synthesis and characterization of a Ni(II) metal‐based gel based on a fluorescent bidentate N, O‐donor Schiff base ligand F16 [212] . The gel formation process was achieved in triethylamine (TEA) presence employing THF/MeOH solvents.…”
Section: Classification Based On Chemo‐sensing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zn(II), Cu(II), and Hg(II) : The article by Pandey et al showed the synthesis and characterization of a Ni(II) metal‐based gel based on a fluorescent bidentate N, O‐donor Schiff base ligand F16 [212] . The gel formation process was achieved in triethylamine (TEA) presence employing THF/MeOH solvents.…”
Section: Classification Based On Chemo‐sensing Methodsmentioning
confidence: 99%
“…F16. [212] The gel formation process was achieved in triethylamine (TEA) presence employing THF/MeOH solvents. This demonstrated excellent sensitivity to Ni(II) ions, with a clear distinction between 1 : 1 and 1 : 2 stoichiometries, resulting in mechanically stable and unstable gels, respectively.…”
Section: Cr(vi) and Fe(iii)mentioning
confidence: 99%
“…Notably, different organic/inorganic moieties (Schiff base and hydrazone derivatives) as LMMGs interact with their metal coordinating sites through versatile supramolecular noncovalent interactions to form a metallogel network. Due to their easy availability and cost-effectiveness, transition-metal ions (Cd 2+ , Zn 2+ , Cu 2+ , Ni 2+ , Co 2+ ) have been used toward the synthesis of economically feasible functional gelators. Nickel­(II) ion finds many effective applications such as in coordination complex formation, polymer synthesis, catalysis, quantum dot formation, gas adsorption, paramagnetic alloys, and optoelectronic/semiconducting electronic devices. Moreover, Ni­(II)-induced metallogels exhibit specific features such as magnetic, thermal, biological, and self-healing properties in supramolecular chemistry. , A urea-functionalized pyridyl dicarboxylate-based Ni­(II) gel has demonstrated potential for drug delivery via H···bonding and π···π stacking interactions . In addition, a tetra- and hexa-podal carboxylic acid/amide-based Ni­(II)-based gel was developed that exhibited chemical interactions for dyes and CO 2 adsorption .…”
Section: Introductionmentioning
confidence: 99%
“…Duplicating the nature, this domain of supramolecular phenomena epitomizes versatile and auspicious fields of research, manifesting an extensive array of scientific and technological advancements . The genesis of lab-made metallogels entails a self-assembling symphony of metal-containing fragments and gelator molecules, orchestrating an exquisite three-dimensional network in the presence of a suitable immobilized-solvent, resulting in a gel-like arrangement. , These versatile supramolecular systems display a wide array of interplaying interactions contributing to their unique properties and applications. Foremost among these interactions is the metal−ligand coordination, wherein metal ions precisely coordinate with ligands nestled within the gel matrix. ,, This coordination imparts structural stability to the gel network, allowing it to self-assemble into intricate architectures. Other essential supramolecular interactions involving hydrogen bonding, coordination-driven self-assembly, host–guest interactions, electrostatic, π−π stacking, hydrophilic, and hydrophobic interactions, van der Waals, etc., are well documented to influence its mechanical properties in the gel state. The resulting metallogel exhibits a semisolid viscoelastic behavior with a high degree of structural integrity.…”
Section: Introductionmentioning
confidence: 99%